Pijat Bayi terhadap Kualitas Tidur pada Bayi Usia 1-12 Bulan - Erlina Erlina; Fatiyani Fatiyani; Nizan Mauyah (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the effect of infant massage on the sleep quality of infants aged 1-12 months in Langa Village, Syamtalira Bayu District, North Aceh District. The research method was pre-experimental with a one-group pretest-posttest design. The study found that 92% of mothers did not massage their babies, with the pre-test results for the quality of their baby's sleep in the "Enough" and "Not enough" conditions. After the baby massage treatment, 100% of the babies experienced an increase in sleep quality to a 100% "Good" state. The results of the bivariate test obtained a p-value = 0.000. In conclusion, infant massage affects the sleep quality of infants aged 1-12 months in Langa Village, Syamtalira Bayu District, and North Aceh District. Keywords: Babies, Sleep Quality, Baby Massage